2016
DOI: 10.3390/md14080148
|View full text |Cite
|
Sign up to set email alerts
|

Undaria pinnatifida and Fucoxanthin Ameliorate Lipogenesis and Markers of Both Inflammation and Cardiovascular Dysfunction in an Animal Model of Diet-Induced Obesity

Abstract: Brown algae and its carotenoids have been shown to have a positive influence on obesity and its comorbidities. This study evaluated the effect of Undaria pinnatifida and fucoxanthin on biochemical, physiological and inflammation markers related to obesity and on the expression of genes engaged on white adipose tissue lipid metabolism in a murine model of diet-induced obesity. The treatments improved energy expenditure, β-oxidation and adipogenesis by upregulating PPARα, PGC1α, PPARγ and UCP-1. Adipogenesis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 49 publications
3
62
0
2
Order By: Relevance
“…In addition, several in vivo studies support the positive effect of seaweed products when consumed directly or as dietary supplements on health by reducing body weight (Okada et al, 2011), lipid oxidation (Grasa-López et al, 2016), oxidative stress and insulin resistance (Tong et al, 2015). Seaweed extracts have also shown antimicrobial (Cox, Abu-Ghannam, & Gupta, 2010), anti-inflammatory (Han et al, 2015), anti-diabetic (Kang et al, 2013) and prebiotic effects (Charoensiddhi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several in vivo studies support the positive effect of seaweed products when consumed directly or as dietary supplements on health by reducing body weight (Okada et al, 2011), lipid oxidation (Grasa-López et al, 2016), oxidative stress and insulin resistance (Tong et al, 2015). Seaweed extracts have also shown antimicrobial (Cox, Abu-Ghannam, & Gupta, 2010), anti-inflammatory (Han et al, 2015), anti-diabetic (Kang et al, 2013) and prebiotic effects (Charoensiddhi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Por se tratar de um modelo simples e que mais se assemelha à realidade da obesidade em humanos, os modelos animais de obesidade obtidos através de dietas hipercalóricas tem sido amplamente utilizados no estudo das alterações metabólicas ligadas à obesidade (Lai, Chen et al, 2015;Sladek, Stevens et al, 2015; Grasa-Lopez, Miliar-Garcia et al, 2016). Nestes modelos, os animais reproduzem melhor o estado de obesidade comum em humanos do que a maioria dos modelos geneticamente modificados e podem ser a melhor escolha para testar estratégias terapêuticas (Lutz e Woods, 2012;Barrett, Mercer et al, 2016).…”
Section: Dietas Suplementadas Com Gordura Ou Carboidratosunclassified
“…Em nossa pesquisa, encontramos uma série de estudos (24) que utilizaram desta metodologia para indução da obesidade (Hvid, Blouin et al, 2013;Sanghez, Razzoli et al, 2013;Oliveira, Santos et al, 2014;Saleh, El-Maraghy et al, 2014;Donner, Elliott et al, 2015;Kulkarni, Jaji et al, 2015;Lai, Chen et al, 2015;Sladek, Stevens et al, 2015;Baldassano, Amato et al, 2016;Ferramosca, Conte et al, 2016;Grasa-Lopez, Miliar-Garcia et al, 2016;Marin, Rosso et al, 2016;Tung, Lin et al, 2016;Ezquer, Bahamonde et al, 2017;Nascimento-Sales, Fredo-Da-Costa et al, 2017;Ojo, Simenson et al, 2017;Oliveira, Chaves et al, 2017;Porras, Nistal et al, 2017;Sadowska, Gebczynski et al, 2017;Sharma, Kim et al, 2017;Xu, Ye et al, 2017;Li, Feng et al, 2018;Tasyurek, Eksi et al, 2018;Watanabe, Kumazaki et al, 2018) (Tabela 1).…”
Section: Dietas Suplementadas Com Gordura Ou Carboidratosunclassified
“…For example, feeding of seaweed powder of Sargassum polycystum suppressed weight gain in rats fed with high fat diet and reduced the plasma levels of cholesterol and triacylglycerols [20]. In another study, feeding of the brown seaweed Undaria pinnatifida showed positive effects on body weight gain, energy consumption, and serum levels of glucose and insulin in diet-induced obese mice [21]. In addition, there was decreased expression of the inflammatory marker interleukin-6 (IL-6), increased energy expenditure, and decreased lipogenesis that resulted in more and smaller adipocytes in retriponeal tissue.…”
Section: Seaweeds As Food and Their Potential Anti-obesity Effectsmentioning
confidence: 99%
“…Fucoxanthinol, a metabolite of fucoxanthin, was also reported to suppress low-grade inflammation in adipocytes, as indicated by its effect in reducing TNF-α and MCP-1 mRNA suppression in a co-culture of adipocytes and macrophage cells [48]. A more recent study by Grasa-Lopez et al (2016) using a mouse model further proved that fucoxanthin decreased WAT mass, and decreased serum triacylglycerols but increased serum HDL cholesterol [21]. Other beneficial effects observed were improved insulin resistance, reduced blood pressure, increased expression and decreased serum levels of adiponectin, and decreased expression of leptin.…”
Section: Algal Compounds With Anti-obesity Effectsmentioning
confidence: 99%